Dinamika Kelompok dan Pengaruh Terhadap Kinerja Organisasi - Seftina, Ayumi; Sabila, Fadlah Putri; Syaharani, Namira; Tanjung, Nurmaulisa; Mukhlasin, Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Group dynamics in the context of modern organizations and their impact on organizational performance. Group dynamics is the study of interaction, communication, and relationship dynamics between individuals in a group. These factors greatly influence how groups work together, collaborate, and achieve common goals. On the other hand, organizational influences include organizational structure, culture, and policies that influence group behavior and dynamics. The importance of group dynamics and how organizational influences can moderate these dynamics. As well as how to have practical implications in effective management in managing group dynamics, creating an inclusive and supportive work culture, and ensuring that the organizational structure supports collaboration and innovation. Healthy group dynamics, including open communication, trust, and effective conflict resolution, significantly improve overall group and organizational performance.